Nepal : 2005 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Nepal. (IMF Staff Country Reports; Country Report ;, 2006)
This 2005 Article IV Consultation highlights that Nepal's economic growth has been affected by the political turmoil and conflict, although inflation has remained moderate, and international reserves are adequate. Real GDP growth averaged 2 percent during 2000/01-2004/05, compared with the 1990s when growth in agricultural productivity and significant trade liberalization contributed to average real GDP growth of 5 percent. Inflation has remained in the low single digits, although it rose to 7 3/4 percent in mid-October 2005. The overall and domestically financed deficits remained limited in 2004/05.